Edlink LMS–Assisted Blended Learning: Its Impact on Students’ Physics Conceptual Understanding and Self-Regulated Learning - Nasar, Adrianus; Pau, Maria Evilina; Boleng, Agustina (Jurnal Pendidikan Fisika, 2026)
The rapid digitalization of higher education has created an urgent need for learning models that not only enhance students’ conceptual understanding but also foster their capacity for independent learning, particularly in physics education. In this context, integrating blended learning with a Learning Management System (LMS) offers a promising strategy to support more interactive, flexible, and student-centered instruction. This study aimed to examine the effect of blended learning, assisted by the Edlink LMS, on students’ conceptual understanding in physics and Self-Regulated Learning (SRL). The study employed a quantitative approach using a quasi-experimental design with a single-group pretest-posttest model. The participants were 32 students in the Physics Education Study Program at Universitas Flores. Data were collected using a four-tier diagnostic test to measure conceptual understanding and an expert-validated SRL questionnaire. The data were analyzed through descriptive statistics, normality and homogeneity tests, paired-sample t-test, and N-Gain analysis. The findings showed that students’ average score in physics conceptual understanding increased from 49.65 to 82.27, while the average SRL score improved from 50.27 to 83.18. The paired-sample t-test indicated a statistically significant difference between pretest and posttest scores (p < 0.05), and the N-Gain values for conceptual understanding (0.65) and SRL (0.66) were both categorized as moderate. These results indicate that Edlink-assisted blended learning was effective in improving both cognitive achievement and learning independence. The novelty of this study lies in its focus on Edlink as a local LMS and in its simultaneous examination of conceptual understanding and SRL within physics education. In conclusion, integrating Edlink into blended learning provides an effective, contextually relevant approach to improving the quality of physics instruction. This study contributes to physics education by offering empirical evidence that local digital platforms can support the development of adaptive, independent, and conceptually competent future physics educators.